1982
DOI: 10.1111/j.1600-0676.1982.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

The pathology of hepatitis A in man

Abstract: ABSTRACT— Liver biopsies from 17 patients with serologically established hepatitis A were examined by light microscopy. Biopsies were taken from 2 to 27 weeks after onset of symptoms. All showed acute hepatitis, usually with centrilobular lesions but also commonly with a striking portal and periportal inflammatory reaction, resembling that seen in chronic active hepatitis. The infiltrate was rich in plasma cells. Centrilobular cholestasis was common and occasionally severe. Neither cholestasis nor the periport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Nevertheless, at present most pathologists agree that periportal piecemeal necrosis suggests eventual transition to chronic hepatitis (21). An exception is hepatitis A in which severe periportal necrosis is common but is never followed by chronic hepatitis (22). There is considerable argument whether necrosis bridging central and portal canals has prognostic significance.…”
Section: Changing Concepts Of the Evolution Of Chronicmentioning
confidence: 99%
“…Nevertheless, at present most pathologists agree that periportal piecemeal necrosis suggests eventual transition to chronic hepatitis (21). An exception is hepatitis A in which severe periportal necrosis is common but is never followed by chronic hepatitis (22). There is considerable argument whether necrosis bridging central and portal canals has prognostic significance.…”
Section: Changing Concepts Of the Evolution Of Chronicmentioning
confidence: 99%
“…Furthermore, previous studies have primarily focused on the pathology of HAV hepatitis in liver biopsy specimens before progression to liver failure. 3,5,6,8 The most consistently observed features in explanted livers were minimal to severe hepatocyte necrosis with predominant distribution in zone 1 and 2, and unremarkable portal inflammation. The previous studies of liver biopsies reported less conspicuous parenchymal changes, prominent portal inflammation with predominantly plasma cell infiltration, moderate to severe cholestasis and periportal hepatocyte necrosis.…”
Section: Discussionmentioning
confidence: 90%
“…The previous studies of liver biopsies reported less conspicuous parenchymal changes, prominent portal inflammation with predominantly plasma cell infiltration, moderate to severe cholestasis and periportal hepatocyte necrosis. 3,5,9 The histopathologic differences might be attributable to multiple factors leading to diverse clinical severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…polymerase) protein. 188,189 In the rare fulminant form of hepatitis A, the histological features are those of panlobular necrosis, with microvesicular fatty change in surviving hepatocytes noted in some cases (Fig. X antigen may be found in tumour cells in the absence of other viral proteins.…”
Section: Molecular Virologymentioning
confidence: 99%